2016
DOI: 10.1021/jacs.6b05572
|View full text |Cite
|
Sign up to set email alerts
|

Highly β-Selective Cyclopolymerization of 1,6-Heptadiynes and Ring-Closing Enyne Metathesis Reaction Using Grubbs Z-Selective Catalyst: Unprecedented Regioselectivity for Ru-Based Catalysts

Abstract: It is well-known that Ru-based Grubbs catalysts undergo a highly selective α-addition to alkynes to promote exo-cyclization during ring-closing enyne metathesis (RCEYM) or to produce conjugated polyenes containing five-membered rings during the cyclopolymerization (CP) of 1,6-heptadiynes. There are a few reports of β-selective addition to alkynes using Schrock catalysts based on Mo but none for readily accessible and easy-to-use Ru-based catalysts. We report the first example of β-selective addition to alkynes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 98 publications
(52 reference statements)
3
41
0
Order By: Relevance
“…Cyclopolymerization (CP) of α,ω -diyne derivatives is a powerful tool for preparing substituted polyacetylenes. Early studies regarding CP used ill-defined catalysts, including Ziegler–Natta, MoCl 5 , and WCl 6 catalysts, until the first breakthrough by the Schrock group and later by the Buchmeiser group demonstrating living CP using well-defined Mo-based olefin metathesis catalysts. Subsequently, the utility of CP broadened when user-friendly Ru-based catalysts were shown to promote living CP. Extensive studies have been conducted using 1,6-heptadiyne monomers, yielding five- or six-membered rings (in a random or highly regioselective fashion) in the conjugated backbone via α - , or β -addition, , respectively. Moreoever, recent studies have expanded the scope of CP where 1,7-octadiyne and 1,8-nonadiyne derivatives were used to successfully produce polyacetylenes containing six- and seven-membered rings via α -addition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopolymerization (CP) of α,ω -diyne derivatives is a powerful tool for preparing substituted polyacetylenes. Early studies regarding CP used ill-defined catalysts, including Ziegler–Natta, MoCl 5 , and WCl 6 catalysts, until the first breakthrough by the Schrock group and later by the Buchmeiser group demonstrating living CP using well-defined Mo-based olefin metathesis catalysts. Subsequently, the utility of CP broadened when user-friendly Ru-based catalysts were shown to promote living CP. Extensive studies have been conducted using 1,6-heptadiyne monomers, yielding five- or six-membered rings (in a random or highly regioselective fashion) in the conjugated backbone via α - , or β -addition, , respectively. Moreoever, recent studies have expanded the scope of CP where 1,7-octadiyne and 1,8-nonadiyne derivatives were used to successfully produce polyacetylenes containing six- and seven-membered rings via α -addition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The first β-selective CP producing six-membered rings was reported by the Schrock group in 1996, using modified Mo catalysts,37,38 but no follow-up studies have been reported. Recently, our group demonstrated the first β-selective CP using a user-friendly, Ru-based Grubbs Z -selective catalyst39 to generate conjugated polymers containing six-membered rings, with 67–95% β-selectivity 40. Notably, a new catalyst Ru1 containing a dithiolate ligand, developed by the Hoveyda group,41 exerted far higher β-selectivity in CP of 1,6-heptadiyne monomers (85–99% β-selectivity), generating mainly six-membered conjugated polyenes bearing comparable thermal properties to the five-membered counterparts 42.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a highly efficient living cyclopolymerization employing the third-generation Grubbs catalyst ( Ru1 ) to afford conjugated polyenes consisting of five-membered rings with excellent molecular weight control and narrow dispersity. Interestingly, Grubbs’ Z -selective catalyst ( Ru2 ), which carries a chelating N -heterocyclic carbene (NHC) ligand, gave β-addition products, forming conjugated polyenes made of six-membered rings with a respectable selectivity of 70–85% at ambient conditions . Thus, for both the Schrock- and Grubbs-type catalysts, regiocontrol is possible.…”
Section: Introductionmentioning
confidence: 99%